PENGARUH PEMBERIAN KONSENTRASI PUPUK ORGANIK CAIR DAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN LABU MADU (Cucurbita moschata): PEMBERIAN KONSENTRASI PUPUK ORGANIK CAIR DAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN LABU MADU (Cucurbita moschata) - Sapto Riyadi; Priyono Priyono; Kharis Triyono (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
Thisi istudyi ioni ithei ieffecti iofi iconcentrationi iofi iliquidi iorganici ifertilizeri iandi igoati imanurei ioni ithei igrowthi iandi iyieldi iofi ibutternuti isquashi i(Cucurbitai imoschata),i iaimsi itoi ideterminei ithei iinteractioni iofi igivingi iconcentrationi iofi iNASAi iliquidi iorganici ifertilizeri iandi igoati imanurei ioni ithei igrowthi iandi iyieldi iofi ibutternuti isquashi i(Cucurbitai imoschata),i icarriedi iouti ioni iMayi i2021i itoi iAugusti i2021,i iini iBului iHamlet,i iNgromoi iVillage,i iNawangani iDistrict,i iPacitani iRegencyi iwithi iani ialtitudei iofi i1000i imi iabovei iseai ileveli iandi ithei isoili itypei iisi ilatosol.i iThisi istudyi iusedi iai icompletelyi irandomizedi idesigni i(CRD)i imethodi iwhichi iwasi iarrangedi iini iai ifactoriali imanneri iconsistingi iofi i16i itreatments,i ieachi itreatmenti irepeatedi i3i itimes.i iThei ifertilizersi iusedi iarei iNASAi iliquidi ifertilizeri iandi igoati imanure.i iThei idatai ifromi ithisi iresearchi iwerei ianalyzedi ibyi iDUNCANi itesti iati i5%i ilevel.i iParametersi iobservedi iincludedi iplanti ilength,i inumberi iofi ileaves,i ileafi iwidth,i inumberi iofi itendrils,i ifloweringi itime,i ifruiti iweight,i ifruiti icircumference,i ifruiti ilength,i inumberi iofi ifruitsi iperi iplant.i iThei iresultsi ishowedi ithat:i iNASA'si iliquidi iorganici ifertilizeri ididi inoti ihavei iai isignificanti ieffecti ioni ialli iobservations.i iGoati imanurei ihadi iai isignificanti ieffecti ioni iplanti iheight,i inumberi iofi ileaves,i ileafi iwidth,i inumberi iofi itendrils,i ifloweringi itime,i ifruiti iweight,i ifruiti ilength,i ifruiti icircumference.i iThei iinteractioni ibetweeni iNASAi iliquidi iorganici ifertilizeri i(N)i iandi igoati imanurei i(K)i ididi inoti ihavei iai isignificanti ieffecti ioni ialli iparameters.i iGoati imanurei i(K3)i igavei ithei ihighesti iplanti ilength,i inamelyi i158.13i icm,i inumberi iofi ileavesi i12i ipieces,i ileafi iwidthi i17.06i icm,i inumberi iofi itendrilsi i10i istrands,i iwheni ifloweringi i41i idaysi iafteri iplanting,i ifruiti iweighti i866i igrams,i ifruiti ilengthi i19.17i icm,i iandi ifruiti icircumferencei i26i icm.